PENGARUH PEMBERIAN SOLID KELAPA SAWIT DAN NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG TANAH (Arachis hypogaea L.) - Damanik, Dedi Setiawan; Murniati, Murniati; Isnain, Isnain (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to obtain the respon of solid and NPK fertilizer and to get the best dossage of solid and NPK for peanut produduction. The experiment was conducted at the Faculty of Agriculture, Universitas Riau, from November 2016 to February 2017 using factorial of Completely Random Design the first factor was residu palm oil solid (13, 26 and 39 ton/ha) and second factor was NPK fertilizer (100, 200 and 300 kg/ha). The parameters observed were the time of flowering, number of effective nodules, the weight of effective nodules, number of primary branches, number of pods, the percentage of the voluminous pods, the weight of 100 seeds and production/m2. Data obtained were analyzed using variance analysing and followed by Duncan's multiple-range test of 5%. The results showed that interaction of solid and NPK showed significant response on all parameters except time of flowering and number of primary branches. The single factor of solid showed a significant response on all parameters except the percentage of pods, while the single factor of NPK showed a significant response on all parameters except the time of flowering, the percentage of pods and weight of 100 seeds. palm oil solid 26 ton/ha and NPK 200 kg/ha the best response on the number of pods, percentage of pods, weight of 100 seeds and weight of production/m2. Keywords: peanut, palm oil solid, NPK fertilizer